Eriobotrya japonica (Thunb.) Lindl.: Ethnomedicinal uses, phytochemical contents and pharmacological properties: A Review - El Aouni, Nabia; Dahmani, Widad; Ali, Amanat; Evariste Akissi, Louis Zachée; Dib, Ikram; Legssyer, Abdelkhaleq; Sahpaz, Sevser; Ziyyat, Abderrahim (Ethnobotany Research and Applications, 2025)
Background: Eriobotrya japonica (Thunb.) Lindl. (E. japonica) is a small evergreen tree, commonly called loquat, that belongs to the Rosaceae family. It is widespread in Asia, Mediterranean region and on the American continents. Depending on its origin and source, loquat is divided into two main types Chinese loquat and Japanese loquat and many varieties have been developed from them. Although no authentic data is available on its global production, in 2019, it was estimated to be around 1.58 million tons. This review highlights the morphology, ecology, ethnomedicinal uses, phytochemical constituents and biological activities of E. japonica. Methods: Extensive literature searches were carried out using scientific databases like Scopus, ScienceDirect, Springer, Web of Science, JSTOR, PubMed and Google Scholar. Results: Different parts of this plant (leaves, fruit, bark, stem, flowers and roots) are used in folk medicine to treat respiratory disorders, diabetes, kidney illnesses and cardiovascular problems. E. japonica is a rich source of many bioactive components such as polyphenols, flavonoids, terpenoids, carotenoids, minerals, vitamins and dietary fibers. These bioactive compounds act as antioxidant, anti-inflammatory, antidiabetic, cardioprotective, anticancer, antidiarrheal and hepatoprotective and are considered for its pharmacological effects. Studies on animals have shown that various parts of loquat and their aqueous extracts are not toxic even at high doses (aqueous extracts of loquat leaves (LLE) at 5000 mg/kg BW). Conclusions: This review comprehensively summarizes the botany, ecology, phytochemistry, and biological activities of E. japonica. It also provides some practical provision for future research on this plant. Keywords: Loquat; Eriobotrya japonica; Rosaceae; Ethnomedicinal uses; Phytochemistry; Pharmacology; Toxicity